Chapter 3
Initial Value Problems





Chapter Summary

Formulas

This summary repeats derivative formulas from Chapter 2, but with some reorganization and renaming.

The Constant Multiple Rule

d d t A f ( t ) = A d f d t , for any constant A

The Sum Rule

d d t f ( t ) + g ( t ) = d f d t + d g d t

The Difference Rule

d d t f ( t ) - g ( t ) = d f d t - d g d t

Derivatives of exponential functions

d d t e k t = k e k t , for any constant k
d d t b t = ( ln b ) b t , for any positive constant b

Derivatives of Power Functions (the Power Rule)

d d t t n = n t n - 1

Derivatives of polynomial functions

Combine the Power Rule, the Constant Multiple Rule, and the Sum Rule.
Go to Back One Page Go Forward One Page

Go to Contents for Chapter 3Contents for Chapter 3